Squamous Cell Carcinoma Developing in a Cutaneous Lichen Planus Lesion: A Rare Case - Saptarshi Ghosh; Sivasankar Kotne; P. B. Ananda Rao; S. P. V. Turlapati; Dillip Kumar Soren (Case Reports in Dermatological Medicine)
Lichen planus is a benign disorder characterized by an itchy, noninfectious skin rash. Though lichen planus is a common papulosquamous disorder affecting about 1-2% of the population, neoplastic transformation of cutaneous lichen planus lesions occurs very rarely and should be borne in mind while treating nonhealing longstanding lesions of lichen planus. Studies suggest an estimated 0.3–3% risk of malignancy in patients with oral lichen planus, however, cutaneous lichen planus does not carry an increased risk of malignant degeneration. We present a case of a 36-year-old male with a 10-year-long history of hypertrophic lichen planus who presented with a nonhealing ulcer in the left popliteal fossa. The patient underwent wide local excision with superficial skin grafting. Postoperative histopathological examination revealed verrucous squamous cell carcinoma complicating lichen planus. In view of underlying structure involvement, adjuvant radiation therapy was given. This case is being reported to emphasize the infrequent possibility of development of malignancy in cutaneous lichen planus, especially if it presents as a longstanding, nonhealing, itchy lesion with patchy areas of depigmentation in the lower limbs.